Embedded PZT sensors for monitoring formation and crack opening in concrete structures. (September 2021) - Kocherla, Amarteja; Duddi, Murali; Subramaniam, Kolluru V.L.
Highlights: Embeddable PZT sensor developed for internal stress wave measurements in concrete. Formation, propagation and opening of a discrete, localized crack in concrete monitored with embedded sensors. Stress wave measurements performed using pairs of distributed sensors. Attenuation of signals are sensitive to crack opening in stress wave path. Crack-induced physical discontinuity in the unloaded state detected in attenuation measurements. Abstract: An application for sensing the stress-induced localization of damage in the form of a discrete crack in a concrete substrate is developed using embedded PZT patches. Stress-wave measurements are obtained through the stages of damage localization leading to crack formation, propagation, and opening of the discrete, localized crack in the concrete. A self-compensating attenuation factor is proposed to quantify the changes in stress waves produced by the material discontinuity introduced by cracking in concrete. The attenuation factor measurements provide a sensitive indication of displacement discontinuity introduced by a crack in the stress wave path. Displacement discontinuity in concrete associated with a crack opening smaller than 10 μm in the loaded state is detected in the attenuation factor measurements even after the removal of stress. The embedded PZT sensors can continuously monitor concrete structures for indications of crack formation before visual indication.